Improved Nitrogen Use Efficiency and Greenhouse Gas Emissions in Agricultural Soils as Producers of Biological Nitrification Inhibitors - Saud, Shah; Wang, Depeng; Fahad, Shah (Frontiers in Plant Science, 2022)
Fertilization is one of the main means to improve agricultural productivity, and improving the utilization rate of nitrogen fertilizer is one of the core issues of fertilizer application. Nitrate loss and nitrous oxide (N2O) emissions caused by nitrification and denitrification are the main reasons for the low utilization rate of nitrogen fertilizers. N2O is a greenhouse gas that has caused a sharp increase in global temperature. Biological nitrification inhibition refers to the ability to release natural compounds that inhibit nitrification from plant roots. The natural compounds released are called biological nitrification inhibitors (BNI), which specifically inhibit the activity of microorganisms in soil nitrification. Biological nitrification inhibitors can significantly improve rice (Oryza sativa), corn (Zea mays) and other crops yield 5% to 10%, which can increase the nitrogen utilization rate of corn by 3.1%, and also reduce greenhouse gas N2O emissions; compared with plants that do not produce BNI, the amount of N2O released can be reduced by up to 90%. The name released by Brachiaria humidicola (Brachiaria humidicola) BNI of brachialactone accounts for 60% to 90% of the total inhibitory effect in its inhibition of nitrification. In summary, it can be seen that biological nitrification inhibitors are inhibiting nitrification, improving nitrogen utilization and crop yield, and reducing greenhouse gas emissions play an important role. This article reviews the known release of biological nitrogen plants that inhibit nitrification and plants that can inhibit soil nitrification, and further discuss the important role of biological nitrification inhibition in agricultural systems.